Development of instrumented oedometer incorporated with bender element and electrical conductivity - Mofreh Gubran, Mohammed Mansoor (2018)
Soft soils are normally associated with high moisture content and fine-grained particles possessing poor geotechnical properties such as low shear strength and high compressibility. Solidification, using hydraulic binders could be adopted to improve these poor properties. The compressibility of soil is quantified by the settlement reduction due to the application of vertical load. Usually, the compressibility test is conducted on undisturbed saturated soils using standardised oedometer. In this study, an instrumented oedometer was developed by incorporating bender element transducers and electrical conductivity probe to investigate and correlate the compressibility, shear wave velocity (Vs) and electrical conductivity (EC) characteristics of solidified dredged marine clay and refined kaolin. Ordinary Portland cement was used at 5 %, 10 % and 15 % by dry weight of soil as a solidification agent. All specimens were mixed at twice the liquid limit. Prior to testing, all solidified specimens were cured for 7 days. It was found that Vs increased continuously with further curing time whereas EC increased during the first day and decreased with further curing. The compressibility was reduced and yield stress was developed as the cement content increased. Vs and EC showed good correlation with applied stress during the loading stage as the strain increased. For all loading stages, Vs increased when the strain increased while EC decreased as the strain increased. Similarly, Vs, EC and e showed good relationship as the vertical stress increased. These results showed good relationship and strong correlations between the compressibility parameters and Vs and EC measurements which give some insights on the solidification mechanism and improvement of stiffness. These results also confirmed that the instrumented oedometer incorporated with bender element and electrical conductivity probes can be applied on soft soils to monitor the compressibility behaviour at micro level. Moreover, the obtained relationships could be adopted in numerical modelling as well design analysis of similar soils in situ.